Classificação de recursos trabalhistas: uma análise crítica da classificação decimal de direito com vistas a uma proposta metodológica de extensão - Martinez, Marisa Luvizutti Coiado [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
The organization and representation of the knowledge registered or socialized implies the usage of documentary languages, in a field that bibliographic classification systems stand in bold relief, which not only determine the physical localization of a document in an information unit but also represent the area of speciality related to the subject of the document. In the specific case of Law, the speciality and the update of these instruments become determinative, because it is a field in constant development, with a fast embodiment of new terms in the speciality area. In the specific case of Brazil, there is the Law Decimal Classification, which not even in its more recent edition (2002) foresee specific subdivision of labor law procedures. This is what generates the impossibility of the representation of the subjects of this juridical sphere, especially in working resources stance, which have a great thematic specificity and intense documentary production. In this way, we tried to make a comparison between the labor law procedures area (by the identification and act hierarchizing of its terms according to Brazilian doctrine) and the conceptual and notational structure of Law Decimal Classification, so as to provide methodological subsidy to the enlargement and update process of the structure in the working resources field. To do that it was used doctrinaire literatures, because they are considered as sources to the knowledge structuring in the area. From the resources characterization in Brazilian labor law procedures field, we entered in the approach of information subject treatment, with a special view about the notational terminological structure of Law Decimal Classification, which presents a symbiosis between the structural aspect o the Dewey Decimal Classification and the conceptual aspect of the Universal Decimal Classification... (Complete abstract, click electronic address below)

A organização e representação do conhecimento registrado ou socializado pressupõe a utilização de linguagens documentárias, no âmbito das quais destacam-se os sistemas de classificação bibliográficos que não apenas determinam a localização física de um documento em uma unidade de informação como também representam a área de especialidade relativa à temática do mesmo. No caso específico do Direito, a especificidade e a atualização desses instrumentos torna-se determinante, visto ser um campo em constante desenvolvimento, com rápida incorporação de novos termos na área de especialidade. No caso específico do Brasil, dispõe-se da Classificação Decimal de Direito, que, nem mesmo em sua edição mais recente (2002) prevê subdivisões específicas para a área de Direito Processual do Trabalho. Isso que gera a impossibilidade de representação dos assuntos desse ramo jurídico, principalmente no caso dos recursos trabalhistas, que possuem grande especificidade temática e intensa produção documental. Dessa forma, objetivou-se realizar um cotejo entre a área de Direito Processual do Trabalho (por meio da identificação e hierarquização de seus termos de acordo com a doutrina brasileira) e a estrutura conceitual e notacional da Classificação Decimal de Direito, de modo a fornecer subsídios metodológicos para o processo de extensão e atualização da mesma no âmbito dos recursos trabalhistas. Para tanto, utilizou-se de obras doutrinárias, por serem consideradas como fontes para a estruturação do conhecimento na área. Partindo da caracterização dos recursos no âmbito do Direito Processual do Trabalho brasileiro, adentrou-se na abordagem do tratamento temático da informação, com especial destaque à estrutura notacional e terminológica da Classificação Decimal de Direito, que apresenta uma simbiose entre o aspecto...
Keywords: Classificação decimal; Direito - Classificação; Direito - Documentação; Recuperação da informação - Direito; Recursos trabalhistas; Decimal Classification; Juridical Documentation; Working Resource